Topical GZ21T Inhibits the Growth of Actinic Keratoses in a UVB-Induced Model of Skin Carcinogenesis - Zachary A. Bordeaux; Justin Choi; Gabriella Braun; Cole Davis; Melika Marani; Kevin Lee; Christeen Samuel; Jackson Adams; Reed Windom; Anthony Pollizzi; Anusha Kambala; Hannah Cornman; et al. (Elsevier, 2023)
Actinic keratoses (AKs) are premalignant intraepidermal neoplasms that occur as a result of cumulative sun damage. AKs commonly relapse, and up to 16% undergo malignant transformation into cutaneous squamous cell carcinoma. There is a need for novel therapies that reduce the quantity and surface area of AKs as well as prevent malignant transformation to cutaneous squamous cell carcinomas. We recently showed that GZ17-6.02, an anticancer agent composed of curcumin, haramine, and isovanillin, inhibited the growth of H297.T cells. This study evaluated the efficacy of a topical formulation of GZ17-6.02, known as GZ21T, in a murine model of AK generated by exposing SKH1 mice to UVR. Treatment of mice with topical GZ21T inhibited the growth of AKs by decreasing both lesion count (P = 0.012) and surface area occupied by tumor (P = 0.002). GZ21T also suppressed the progression of AKs to cutaneous squamous cell carcinoma by decreasing the count (P = 0.047) and surface area (P = 0.049) of lesions more likely to represent cutaneous squamous cell carcinoma. RNA sequencing and proteomic analyses revealed that GZ21T suppressed several pathways, including MAPK (P = 0.025), phosphoinositide 3-kinase-protein kinase B (P = 0.04), HIF-1α (P = 0.016), Wnt (P = 0.025), insulin (P = 0.018), and ERBB (P = 0.016) signaling. GZ21T also upregulated the autophagy-promoting protein AMPK while suppressing proteins such as PD-L1, glutaminase, pAkt1 S473, and eEF2K.